Street kitchens and social lives: an ethnographic study of street food and eating practices in inner-city Johannesburg - Sewpersad, Sapana (My University, 2020)
The making and consumption of food are fundamental secular rituals that make up the everyday. The activity of eating is an inherently social activity. Eating practices and food are always mediated through social relations and vice-versa. This thesis is interested in the phenomenon of street food and economic exchange. Street food is an interesting, common food practice which is ancient and present in every civilisation, globally. Following this, street food is thus an important element that would make up the inner city of Johannesburg. This thesis is interested in interrogating what happens to the highly social events of sharing, giving and accepting food when it is mediated through economic exchange. This thesis seeks to understand how everyday food and eating practices facilitate a relationship between street vendors and their consumers. The main question of this thesis is; What kind of social relationships are formed and performed in the everyday preparing, selling and consuming of street food in downtown, inner-city Johannesburg? Using participant observation and ethnographic methods, this thesis finds that whilst there is a definite economic aspect to vending, food fosters social relationships between vendors and their customers. There is flexibility that is exhibited around price structure, there are cracks in the idea of vending being purely economic as social relationships are a factor in how profits are determined. The act of cooking takes on a maternal aspect, within this setting. This thesis further illustrates how close spatial proximity works to foster domestic commensality amongst the customers of the stall
A research report submitted in partial fulfilment for the degree of Masters of Social Anthropology by Course work and Research Report, in the Department of Anthropology Faculty of Humanities at the University of Witwatersrand, 2020